JAZF1/SUZ12 gene fusion in endometrial stromal sarcomas - Hrzenjak, Andelko (BioMed Central, 2016)
Endometrial stromal sarcomas (ESSs) belong to the rarest uterine malignancies (prevalence category <1-9/1,000,000). According to the new 2014 World Health Organisation (WHO) classification, they are separated into four categories; benign endometrial stromal nodules (ESNs), low grade endometrial stromal sarcomas (LG-ESSs), high-grade endometrial stromal sarcomas (HG-ESSs) and undifferentiated uterine sarcomas (UUSs). Due to heterogeneous histopathologic appearance these tumors still represent diagnostic challenge, even for experienced pathologists. ESSs are genetically very heterogeneous and several chromosomal translocations and gene fusions have so far been identified in these malignancies. To date the JAZF1/SUZ12 gene fusion is by far the most frequent and seems to be the cytogenetic hallmark of ESN and LG-ESS. Based on present literature data this gene fusion is present in approximately 75 % of ESN, 50 % of LG-ESS and 15 % of HG-ESS cases. The frequency of JAZF1/SUZ12 appearance varies between classic ESS and different morphologic variants. This gene fusion is suggested to become a specific diagnostic tool, especially in difficult borderline cases. In combination with the recently described YWHAE/FAM22 gene fusion the JAZF1/SUZ12 fusion could be used to differentiate between LG-ESS and HG-ESS. The purpose of this review is to summarize literature data published in last two and a half decades about this gene fusion, as a contribution to our understanding of ESS genetics and pathogenesis.